EFFECTIVENESS OF THE SEPARATION OF MAGNESIUM AND LITHIUM FROM SEAWATER WITH SODIUM SILICATE PRECIPITATION PROCESS - Latifa Hanum Lalasari; Eko Sulistiyono; Sri Harjanto; Florentinus Firdiyono; Nadya Chrisayu Natasha; Yosephin Dewayani (Metalurgi, 2022)
Experiments have been carried out to separate elements of magnesium and lithium from seawater to produce a lithium concentrate product that is free of magnesium through sodium silicate precipitation processes. In this study, the sample used was seawater taken from the Ancol Lagoon Area, North Jakarta. The sea water used contains 0.1674 ppm lithium ions and 1761 ppm magnesium ions with a high Mg/Li ratio of 10521. The seawater containing high levels of magnesium is not suitable as a raw material for for the manufacture of lithium carbonate (battery active ingredient) prior to initial processing. The research variable was the volume of sodium silicate solution added by 10 ml, 20 ml, 30 ml, 40 ml, 50 ml, 60 ml, 70 ml, and 100 ml which were equivalent to 13%, 27% 40%, 53%, 67%. , 80 %, 93%, and 107% stoichiometry of magnesium ion and the technique of adding sodium silicate solution included a single stage and multi-stages. From the experimental results, it can be seen that the most effective addition of sodium silicate is the addition of 80% stoichiometry. The sodium silicate precipitation process succeeded in separating magnesium ions and lithium ions from seawater as indicated by a decrease in the Mg/li ratio from 10521 to 64. The obstacle in this study was that there were still many lithium ions that were also precipitated with magnesium silicate during the precipitation process so that the lithium lost in the filtrate reached 82.26% in the single stage process. Therefore, a multi-stage process was carried out with 6 stages of the process that the addition of sodium silicate for each stage was 1/6 of the volume of sodium silicate solution at single stage optimum conditions. The results obtained from the multi-stage process were able to reduce the lithium ion lost in the filtrate to 76.54%. From the results of the study, it can be concluded that efforts to reduce the percentage of lithium ions lost in the filtrate product need to be carried out through the development of a sodium silicate precipitation process.